2012
DOI: 10.1186/1471-2164-13-678
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the type IV secretion system in different strains of Anaplasma phagocytophilum

Abstract: BackgroundAnaplasma phagocytophilum is an intracellular organism in the Order Rickettsiales that infects diverse animal species and is causing an emerging disease in humans, dogs and horses. Different strains have very different cell tropisms and virulence. For example, in the U.S., strains have been described that infect ruminants but not dogs or rodents. An intriguing question is how the strains of A. phagocytophilum differ and what different genome loci are involved in cell tropisms and/or virulence. Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 54 publications
2
51
1
Order By: Relevance
“…As expected, the results showed that the sheep isolate clustered together with Norway variant2 isolate obtained from a lamb. The L610 dog isolate clustered together with isolates from horses, ticks, humans, rodents and dogs but was different from the previously reported Dog2 isolate (Al-Khedery et al, 2012). Finally, as expected, the human NY18 isolate clustered together with other human isolates.…”
Section: Analysis Of Tick Cell Mrna Levels By Real-time Rt-pcrcontrasting
confidence: 66%
See 1 more Smart Citation
“…As expected, the results showed that the sheep isolate clustered together with Norway variant2 isolate obtained from a lamb. The L610 dog isolate clustered together with isolates from horses, ticks, humans, rodents and dogs but was different from the previously reported Dog2 isolate (Al-Khedery et al, 2012). Finally, as expected, the human NY18 isolate clustered together with other human isolates.…”
Section: Analysis Of Tick Cell Mrna Levels By Real-time Rt-pcrcontrasting
confidence: 66%
“…For comparison, the same sequences were obtained for 9 isolates of which the genomes have been sequenced and are available in Genbank. The isolates CRT35 (NCBI reference sequence JFBI01000001; Massung et al, 2007;Al-Khedery et al, 2012) and CRT38 (NCBI reference sequence NZ_APHI00000000) were isolated from I. scapularis ticks, the isolate Dog2 was isolated from a dog (NCBI reference sequence CP006618; Al-Khedery et al, 2012), the isolate JM was obtained from a rodent (NCBI reference sequence CP006617; Al-Khedery et al, 2012), the MRK isolate was obtained from a horse (NCBI reference sequence JFBH00000000; Al-Khedery et al, 2012), the (Katoh and Standley, 2013). After alignment, regions with gaps were removed and 2354 gap-free sites were used in maximum likelihood (ML) phylogenetic analysis as implemented in PhyML (v3.0 aLRT) (Anisimova and Gascuel, 2006;Guindon and Gascuel, 2003).…”
Section: Dna Isolation and Phylogenetic Analysis Of A Phagocytophilumentioning
confidence: 99%
“…8A ). Interestingly, other Rickettsiales genomes encode duplicate ( Orientia , Neorickettsia , Midichloria ) or proliferated ( Wolbachia , Anaplasma , and Ehrlichia ) rvhB2 genes (Nelson et al ., 2008, Gillespie et al ., 2010, Sutten et al ., 2010, Al-Khedery et al ., 2012). Some proliferated RvhB2 genes have become co-opted into a surface antigen family, possibly to cope for the lack of LPS biosynthesis (Gillespie et al ., 2010) .…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%
“…Many RvhB6 proteins across Rickettsiales have repeat regions within the N- and/or C-terminal extensions, and a staggering degree of sequence length and variation across strains of A . phagocytophilum has been reported within a repeat region of one RvhB6 protein (Al-Khedery et al ., 2012) . Remarkably, all four rvhB6 genes of E .…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%
“…We expanded our studies by testing the functionality of chimeric T4CPs composed of TraJ's NTD joined to the soluble domains of VirD4 Ap and VirD4 Wp from A. phagocytophilum and W. pipientis, respectively. Rickettsial species carry T4SS gene clusters, and a growing body of evidence indicates that type IV secretion is a general requirement for intracellular survival and proliferation (10,43,65,66). Identification of T4SS effectors, however, has been hampered by the inability to grow rickettsial species axenically and by lack of robust genetic systems.…”
Section: ϫ8mentioning
confidence: 99%